From art to health action: lessons from a community-based, culturally tailored arts-meets-health educational campaign in Hispanic communities - Urich, Thomas J.; Lee, Woori; Po, Justine; Bookstein, Arthur; Barahona, Rosa; Baezconde-Garbanati, Lourdes (Frontiers in Public Health, 2024)
Stay Connected LA (SCLA) was an artistically driven campaign that centered upon culturally tailored artwork of different mediums to emphasize health promoting behaviors in several communities in Eastern Los Angeles during the early stages of the COVID-19 Pandemic. This campaign used artwork created by local artists for the campaign and relied on the direct feedback on images and public health messaging from Eastern Los Angeles residents. Community residents provided guidance for public health campaigning in predominantly Hispanic communities. We also received invaluable feedback from focus group participants regarding appropriate means of displaying health promotion graphics, useful modes of communication for different age groups, as well as how to get community leaders involved in the outreach process.We believe that this project yielded critical feedback that will further assist in arts-meets-public health campaigning that engages historically underserved communities, particularly people who identify as Hispanic. This campaign also demonstrated the utility of community based participatory research, which enabled community members to be actively involved and supported throughout the campaign. Our goals, methods, and findings directly correlate with community-centered research on health promotion and disease prevention education that targets both the individual and the community. We look forward to being considered by Frontiers Public Health.